2014
DOI: 10.12705/631.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the restiid clade (Poales) and implications for the classification of Anarthriaceae, Centrolepidaceae and Australian Restionaceae

Abstract: Three families, Anarthriaceae, Restionaceae and Centrolepidaceae, are generally recognised in the restiid clade of Poales. A new phylogeny is presented, with fuller sampling of Australian taxa, based on analyses of trnL‐F, trnK and rbcL data from the chloroplast genome. The findings agree with the major groups shown in previous molecular studies but provide a more substantial basis for reviewing the classification at family and generic levels. Anarthriaceae is sister to Restionaceae, with Anarthria sister to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 88 publications
3
52
0
Order By: Relevance
“…The Desmocladus clade was recognised by Briggs and Johnson (1999), being named after its first-named and largest genus, and is supported by analyses of chloroplast DNA data (Briggs et al 2010(Briggs et al , 2014. The clade is characterised morphologically by uninterrupted culm chlorenchyma, lacking pillar cells and sclerenchyma 1 This paper is dedicated to my former colleague Elizabeth Anne Brown (1956Brown ( -2013, remembering especially her notable achievements in the study of bryophytes and Ericaceae, her love of fieldwork, and her service for many years as Scientific Editor of Telopea.…”
Section: The Desmocladus Cladementioning
confidence: 91%
See 2 more Smart Citations
“…The Desmocladus clade was recognised by Briggs and Johnson (1999), being named after its first-named and largest genus, and is supported by analyses of chloroplast DNA data (Briggs et al 2010(Briggs et al , 2014. The clade is characterised morphologically by uninterrupted culm chlorenchyma, lacking pillar cells and sclerenchyma 1 This paper is dedicated to my former colleague Elizabeth Anne Brown (1956Brown ( -2013, remembering especially her notable achievements in the study of bryophytes and Ericaceae, her love of fieldwork, and her service for many years as Scientific Editor of Telopea.…”
Section: The Desmocladus Cladementioning
confidence: 91%
“…Recently Briggs et al (2014) presented a phylogeny of the restiid clade of Poales that included new data and analyses for the largely Australasian subfamily Leptocarpoideae. The phylogeny indicated that the three small Western Australian genera Kulinia B.G.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogeny of Leptocarpoideae presented by Briggs et al (2014) was based on concatenated sequences of trnK and trnL-F with coded indels, analysed by both Bayesian inference and maximum parsimony. Most species are represented by a single sequence for each gene but several are replicated.…”
Section: The Genus Leptocarpusmentioning
confidence: 99%
“…, Briggs and Johnson (1999), Meney et al (1999), Paczkowska and Chapman (2000), Wheeler et al (2002); Meeboldina sp. D, Briggs et al (2014).…”
Section: Diagnosismentioning
confidence: 99%